The intentionality of speech acts and their conflict with the linguistic context (Journal of the College of Basic Education, 2024)
Indirect speech acts are verbs whose perceptive force contradicts the speaker's intent, meaning that one thing is said in literal speech and another thing is intended, and it was taken here.In my research, this is an indirect interrogative, and what is the definition of an interrogative in language and terminology, and I applied that with Qur’anic evidence that contains an indirect interrogative.I touched on the indirect command in the first third of the Holy Qur’an and applied that with Qur’anic evidence, along with defining the command linguistically and terminologically.I also took the indirect prohibition and addressed itTo define the prohibition, language and terminology, taking the Qur’anic evidence that contains an indirect prohibition and the condition that it be in conflict with the linguistic context, as is the title of my dissertation, and this research is drawn from it